2021
DOI: 10.18549/pharmpract.2021.1.2138
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication consultations in community pharmacy: an exploratory study on teams’ performance, client-reported outcomes and satisfaction

Abstract: Background: Community pharmacy teams (CPTs) have an established role in assisting self-medication, contributing to the safe and effective use of non-prescription medicines. Objective: The study aimed to describe CPTs’ performance in self-medication consultation, client-reported outcomes, and satisfaction. A secondary purpose was to develop an explanatory model for better understanding clients’ satisfaction with this service. Methods: Descriptive, cross-sectional exploratory study. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
(50 reference statements)
0
3
0
1
Order By: Relevance
“…This is consistent with some past studies. For instance, Veiga et al (2021) 41 reported that client satisfaction appears to be determined by consultation quality (evaluation score), suggesting the advancement of the pharmacists’ clinical role. Urbonas and Kubilienė (2016) noted that job satisfaction and quality of OTC counseling in Lithuania were dependent on pharmacists’ age.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with some past studies. For instance, Veiga et al (2021) 41 reported that client satisfaction appears to be determined by consultation quality (evaluation score), suggesting the advancement of the pharmacists’ clinical role. Urbonas and Kubilienė (2016) noted that job satisfaction and quality of OTC counseling in Lithuania were dependent on pharmacists’ age.…”
Section: Discussionmentioning
confidence: 99%
“…The monitoring of real-world usage of OTC medicinal products by community pharmacists would be useful to set up appropriate guidelines on the management and tri-age of patients suffering from upper GI symptoms, to improve pharmacovigilance, and the establishment of proper counseling on such medicinal products. Considering that patients expect high-quality counseling on self-medication (Seiberth et al 2021;Veiga et al 2021), the use of evidence-based tools for supporting pharmacists is widely recognized as a key point for improving self-medication care (Moritz et al 2019(Moritz et al , 2021a. At the international level, there are many examples of tools accessible to pharmacists (i.e., algorithms or symptom assessment questionnaires) for these disorders (New Zealand Guidelines Group 2003;Aradottir and Kinnear 2008;Holtmann et al 2011;Tack et al 2014;Showande and Adelakun 2019).…”
Section: Discussionmentioning
confidence: 99%
“… 28 Subsequent studies have shown a very high satisfaction score of individuals following self-medication private consultations, suggesting the advancement of the pharmacists' clinical role in self-care. 29 Other studies conducted in rural settings, have also shown that >85% of patients' beneficiaries of pharmaceutical counselling had their minor health problems solved after one week. 30 …”
Section: Self-care In Community Pharmacies In Portugalmentioning
confidence: 98%